IMPLEMENTASI KURIKULUM MERDEKA MELALUI MODEL PROJECT BASED LEARNING PADA PEMBELAJARAN MATERI PENCEMARAN LINGKUNGAN UNTUK MENINGKATKAH AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK - Andri, Asep; Muhammad Minan Chusni; Chaerul Rohman (Universitas Mataram, 2024)
Abstract: This study aims to obtain information on student activity and improvement of learning outcomes of seventh grade students of SMP PLUS AL-GHONIYYAH. The concept of Classification of Substances with sub-concepts in cycle I indicators of a healthy environment, while cycle II on Natural Indicators. The research was conducted on VIII grade students consisting of 32 people and one teacher. The research subjects were determined based on the consideration of the science teacher with the researcher. Learning model using Project based learning model. Data were obtained through initial tests of students before learning was carried out and final tests after learning, observation activities (performance) of students and activities (achievement) of teachers during learning each cycle, pre tests and post tests to determine student learning outcomes (gain index) each cycle, along with student response questionnaires during the Project-based learning model in learning conducted in class. The learning outcome evaluation tool used is a multiple choice test to capture the increase in student learning outcomes regarding environmental pollution material. Based on the results of the analysis of learning by implementing the Merdeka Curriculum through the Project-based learning model, there was an increase in student activity of 82% (cycle I) and 89% (cycle II), teacher achievement in learning 79.31% (cycle I) to 96% (cycle II, Increased Learning Outcomes in the Affective Domain by 72% (cycle I) and 96% (cycle II), the Cognitive Domain got a gain index of 0.44 (cycle I medium category) to 0.64 (cycle II high category), the Psychomotor domain from 75% (cycle I) to 86% (cycle II). Students' responses to the Project-based learning model in learning a healthy environment have a positive response to liking science 92%, preparing lessons 85%, understanding the material 85%, being grateful that there is a healthy environment in life by 97%, collaborating in groups by 88%. Implementation of the independent curriculum through the Project based learning model can improve students' activities and learning outcomes. Implementation of the 2013 curriculum through the Project-based learning model can improve the activities and results of students' reasoning.